Analysis of the Maharah Kitabah Instrument in the Arabic Language Book VII of the Ministry of Religion - Muhammad Miftah Al-Khalili; Muhammad Rifqi Fauzi; Sahkholid Nasution (Konsultan Jurnal Ilmiah Indonesia, 2025)
This research aims to analyze the maharah kitabah instrument in class VII Arabic books. This research is library research (library study). In this research, there are two data sources used, namely primary and secondary data sources. The primary data source was taken from the Arabic language book questions for class VII Madrastah Tsanawiyah 2020. Meanwhile, secondary data sources were books, journal articles and websites that discussed the analysis of the maharah kitabah instrument as well as supporting references in this research. The data analysis technique uses descriptive analysis techniques. After the data is obtained, the research results are systematically explained. The results of research analysis of the Maharah Kitabah instrument in Arabic books in class VII, stated that in the questions in the Arabic book for class VII Madrastah Tsanawiyah 2020, 11 questions containing the Maharah Kitabah instrument were found, consisting of essay practice questions and multiple choice questions, namely 6 questions consisting of 10 question branches, 1 question has 2 question branches and 4 questions are multiple choice, so it is very suitable for evaluating texts in Arabic language learning and more specifically in the Maharah Kitabah, because in these questions the material related to the questions presented is presented.